Social sustainability: the challenges to the restaurant sector - Maia, Beatriz (2024)
The guarantee of sustainable development has been a growing concern in various economic sectors, particularly from the economic and environmental perspective. In a post-pandemic scenario, the restaurant industry was one of the most affected worldwide and had to undergo abrupt changes to remain operational. Thus, this study primarily focuses on addressing the challenges faced by Human Resources Management (HRM) in attracting and retaining employees in the restaurant sector. This research aims to understand the challenges faced in retaining and attracting talent to restaurants and to explore the strategies that should be adopted to ensure the restaurant’s social. It used a qualitative methodology, with 10 (5 female and 5 male, with a mean age of 35 years old) semi-structured interviews with professionals who chose to leave this profession, to ensure a concerted view of the current state of the sector in the north of Portugal. Through thematic analysis of the interviews, the results identified the current difficulties in attracting and retaining employees in the sector, as well as some HRM strategies that can address these challenges. These findings emerged from the themes 'Special Features of the Restaurant Sector' and 'Attraction and Retention Strategies.' The first theme contextualizes and characterizes the sector's reality, arising from four categories: activity context, company type, the COVID-19 pandemic, and turnover factors. Meanwhile, the second theme presents the attraction and retention strategies that HRM in restaurant companies should implement, while also exploring some challenges faced in designing and implementing these strategies in practice. Specifically, recruitment and selection, compensation and benefits, onboarding, integration and socialization, and career management. In conclusion, social sustainability still has little prominence in the restaurant sector. To become more attractive, the restaurant sector needs to invest in better non-monetary benefits, such as flexible working hours, health insurance, professional recognition, training investment, and career advancement opportunities. This study intends to help companies take measures to improve employee satisfaction and also increase talent retention and new employees’ attraction.